2004
DOI: 10.1162/089892904970799
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of First-Person Perspective as One Constituent of Human Self-Consciousness

Abstract: Taking the first-person perspective (1PP) centered upon one's own body as opposed to the third-person perspective (3PP), which enables us to take the viewpoint of someone else, is constitutive for human self-consciousness. At the underlying representational or cognitive level, these operations are processed in an egocentric reference frame, where locations are represented centered around another person's (3PP) or one's own perspective (1PP). To study 3PP and 1PP, both operating in egocentric frames, a virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
300
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(329 citation statements)
references
References 38 publications
23
300
1
5
Order By: Relevance
“…Whereas previous studies have highlighted the role of integrating motor signals and proprioceptive information (Amorim et al, 2006;Creem-Regehr, Neil, & Yeh, 2007;Keehner, Guerin, Miller, Turk, & Hegarty, 2006;Kessler & Thomson, 2010;Parsons, 1987;Vogeley et al, 2004;Wraga, 2003;Zacks & Michelon, 2005), this study underlines the central importance of vestibular information for embodied perspective taking. These signals may be of particular importance for mental imagery with respect to one's entire body as opposed to imagery for body parts (Parsons, 1987) where motor and proprioceptive mechanisms may predominate.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Whereas previous studies have highlighted the role of integrating motor signals and proprioceptive information (Amorim et al, 2006;Creem-Regehr, Neil, & Yeh, 2007;Keehner, Guerin, Miller, Turk, & Hegarty, 2006;Kessler & Thomson, 2010;Parsons, 1987;Vogeley et al, 2004;Wraga, 2003;Zacks & Michelon, 2005), this study underlines the central importance of vestibular information for embodied perspective taking. These signals may be of particular importance for mental imagery with respect to one's entire body as opposed to imagery for body parts (Parsons, 1987) where motor and proprioceptive mechanisms may predominate.…”
Section: Discussioncontrasting
confidence: 72%
“…This finding suggests that spatial perspective taking involves the embodied transformation of one's body to adopt the imposed perspective. This 'embodied transformation account' is further supported by neuroimaging studies showing the involvement of motorrelated areas during perspective taking and indicating that spatial perspective taking involves comparable neural mechanisms that are involved in actual bodily movements as well (Vogeley et al, 2004;Wraga, Shephard, Church, Inati, & Kosslyn, 2005;Zacks & Michelon, 2005).…”
Section: Introductionmentioning
confidence: 67%
“…It may be that FH's poorer performance on the 3rd person perspective version of the task is due to a deficit in Theory of Mind (ToM) which literally involves 'putting oneself in another person shoes' while searching for the key. Our results support the fMRI literature showing that performance on first versus third person perspective tasks depends on different neural processes (e.g., Vogeley, Ritzl, Falkai, Zilles & Fink, 2004). Of course, we cannot completely rule out the possibility of neglect without a more extensive neuropsychological assessment being carried out.…”
supporting
confidence: 83%
“…Other neuroimaging studies focused on the manipulation of the perspective during mental imagery and revealed activations within a network of brain areas including precuneus, prefrontal cortex, somatosensory cortex [Ruby and Decety, 2001], as well as right premotor cortex, superior temporal cortex, and cingulate cortex [David et al, 2006;Vogeley et al, 2004]. It is likely that subjects imagined changes in perspective and position jointly during most aforementioned studies, independently of whether investigators focused on body transformations or perspective changes.…”
Section: Introductionmentioning
confidence: 99%